2022
DOI: 10.1186/s13063-022-06454-y
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent family support intervention in intensive care units: study protocol for a multicenter cluster-randomized trial (FICUS Trial)

Abstract: Background Family members of critically ill patients face considerable uncertainty and distress during their close others’ intensive care unit (ICU) stay. About 20–60% of family members experience adverse mental health outcomes post-ICU, such as symptoms of anxiety, depression, and posttraumatic stress. Guidelines recommend structured family inclusion, communication, and support, but the existing evidence base around protocolized family support interventions is modest and requires substantiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 120 publications
0
19
0
1
Order By: Relevance
“…We identified eight ongoing trials targeting ICU surrogates faced with end-of-life healthcare decisions (48–55). Interventions include written rounding summaries (48), electronic decision support aids (49, 55) and interactive web-based support tools (50), a cognitive-behavioral intervention (52), early integration of specialty palliative care (51), and enhanced interprofessional ICU care overseen by nurse specialists (53, 54).…”
Section: Resultsmentioning
confidence: 99%
“…We identified eight ongoing trials targeting ICU surrogates faced with end-of-life healthcare decisions (48–55). Interventions include written rounding summaries (48), electronic decision support aids (49, 55) and interactive web-based support tools (50), a cognitive-behavioral intervention (52), early integration of specialty palliative care (51), and enhanced interprofessional ICU care overseen by nurse specialists (53, 54).…”
Section: Resultsmentioning
confidence: 99%
“…Open access of a nurse-led, interprofessional delivered family support intervention (FSI) in Swiss ICUs. 4 Successful implementation of the three FSI components, namely family engagement, support and communication by a family nurse and interprofessional team along the patient pathway is expected to increase the likelihood of clinical effectiveness, and will be critically influenced by the context into which the intervention is introduced, particularly as part of a multisite clinical trial. [5][6][7][8] Specific implementation guidance for integrating FSIs in critical healthcare settings is still scarce.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A Type 1 hybrid trial focuses primarily on the intervention effectiveness outcomes while exploring the context for future intervention implementation (e.g., Wooldridge et al's 10 evaluation of nonadherence in patients who received discharge medication counseling by a pharmacist as part of an RCT; Naef et al 13 evaluation of a multicomponent family support intervention in intensive care settings).…”
Section: Types Of Hybrid Trialsmentioning
confidence: 99%
“…Hybrid trials exist on a continuum, with the three designs varying based on their primary focus and the amount of emphasis on effectiveness versus implementation outcomes (see Table 1 and Figure 1) 11 , 12 : A Type 1 hybrid trial focuses primarily on the intervention effectiveness outcomes while exploring the context for future intervention implementation (e.g., Wooldridge et al's 10 evaluation of nonadherence in patients who received discharge medication counseling by a pharmacist as part of an RCT; Naef et al 13 evaluation of a multicomponent family support intervention in intensive care settings). A Type 2 hybrid trial has a dual focus on intervention effectiveness and implementation outcomes (e.g., Gilmartin et al's 14 evaluation of the effectiveness of the rural transitions nurse program; Hassett et al's 15 implementation of patient‐reported outcomes for symptom management in oncology practice). A Type 3 hybrid trial focuses primarily on implementation outcomes while also exploring effectiveness outcomes as they relate to uptake, integration, and fidelity of the intervention in real‐world settings (e.g., Bonafide et al's 16 evaluation of a safety huddle‐based intervention; Salloum et al's 17 evaluation of clinical decision support for patient‐centered chronic pain management).…”
Section: Types Of Hybrid Trialsmentioning
confidence: 99%